Hubungan antara Tingkat Kecemasan dengan Kepatuhan Minum Obat pada Pasien Kemoterapi Ca Mamae di Rumah Sakit Semarang - Masrokan; Dwi Heppy Rochmawati; Wigyo Susanto (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2025)
Breast cancer is the leading cause of death globally, following heart disease and stroke. One of the most commonly used treatments is chemotherapy, which offers various benefits but also causes physical and mental side effects. One of the psychological side effects often experienced is anxiety. Extreme fear and the threat of death from cancer can affect adherence to treatment. This study aims to assess the relationship between anxiety levels and medication adherence in breast cancer chemotherapy patients at RSUD Semarang. This research used a quantitative approach with a descriptive correlational method, involving 110 participant samples. The questionnaires used for data collection were DASS-42 to measure anxiety levels and MMAS-8 to assess medication adherence. The study was conducted from June 30 to July 31, 2025, in the Oncology Center room of RSUD Sultan Agung Semarang. Bivariate analysis using Pearson's correlation test showed a p-value of 0.001 < 0.05, indicating a significant relationship between anxiety levels and medication adherence in breast cancer chemotherapy patients. The measured correlation coefficient of -0.325** shows a moderately strong negative relationship, meaning that the higher the anxiety level, the lower the patient's adherence to medication. Based on these findings, it is recommended that nurses in the oncology unit provide additional education and support to patients regarding their anxiety. Effective psychological support can help patients reduce anxiety and increase adherence to treatment, which in turn can improve the outcomes of chemotherapy treatment.